Meningkatkan Kualitas Pembelajaran Fikih Melalui Model Snowballing - Uswatun Hasanah (Millah: Journal of Religious Studies, 2015)
The background of this study is the decline of learning outcomes in subjects of  Islamic Religious Education (PAI) in the Class 3 Primary School (SD). Researchers then apply the research methods Snowballing as a class action. The results showed that an increase in student achievement after the applied method Snowballing. This is the show with an average increase of mastery learning from prior to action until after the action. At the stage of pre-cycle average gained 71.48, at this stage of the cycle I gained an average of 83.08, and at this stage of the cycle II gained an average of 85.48. PTK is successful because it has achieved an increase of more than 90% of the value of previously successful over the KKM.